Frontline Demonstrations: An Effective Way to Improve the Performance of Oats Fodder in Doda District of Jammu and Kashmir - Paul, Narinder; Arora, R. K. (Indian Journal of Animal Nutrition, 2018)
The present study was carried out during rabi 2010-11 to 2016-17 in 23 villages across 4 blocks of District Doda of Jammu & Kashmir to assess the performance and outcome of technological interventions promoted through Front Line Demonstrations (FLDs) on fodder oats by Krishi Vigyan Kendra (KVK), SKUAST-J, Doda in temperate Bhaderwah region. All 109 farmers on whose fields FLDs on fodder oats were laid out in an area of 23.2 hectares during the period with Kent and Sabzar varieties of oats, recommended seed rate, seed treatment and application of recommended doses of fertilizers from rabi 2010-11 to 2016-17 constituted the sample for the present investigation. Results of the study reveal that average yield of fodder oats under FLD plots varied from 330.0 Qtl. ha-1 to 403.1 Qtl. ha-1; whereas, under the farmers’ practice, it varied from 238.1 Qtl. ha-1 to 297.5 Qtl. ha-1. Average Technology Gap (TecGp) to an extent of  79.1 Qtl. ha-1, Extension Gap (ExtGp) of 101.5 Qtl. ha-1 and Technology Index (TecInx) of 22  percent were found. An average of 37.5 percent increase in the yield of green fodder has been found over the farmers’ practice, though chemical composition remains similar irrespective of the variety and village or year of harvesting. The incremental increase in yield of fodder oats crop and subsequent increase in net return under Frontline Demonstrations was due to adoption of improved production technology of fodder oats viz; high yielding varieties, seed treatment, recommended seed rate and balanced fertilization. Besides, a significant impact of FLDs has been observed in the District with increase in the area under fodder oats from 50 Ha in 2009-10 to 2250 ha in 2016-17.